Triterpenoids and Phytosterols Isolated from Pluchea Indica L. Leaves - Thi Viet Huong, Do; Minh Giang, Phan; Thi Sim, Hoang; Thi To Chinh, Truong (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2DO - 10.25073/2588-1140/vnunst.4910, 2019)
Abstract : Taraxasterol acetate, 1-dotriacontanol, taraxasterol, stigmasterol, 2-(prop-1-ynyl)-5-(5,6-dihyroxyhexa-1,3-diynyl)thiophene), stigmasterol 3-O-β-D-glucopyranoside, and β-sitosterol 3-O-β-D-glucopyranoside were isolated from the leaves of Pluchea indica and determined with NMR techniques. Taraxasterol acetate, taraxasterol, and stigmasterol could be isolated in high yields from Pluchea indica growing in Gia Lam, Hanoi, Vietnam.  Keywords: Pluchea indica, phytosterol, triterpenoid, taraxasterol, stigmasterol . References : [1] Đỗ Tất Lợi, Những cây thuốc và vị thuốc Việt Nam, NXB Hồng Đức, Thanh Hóa, 2014. [2] H. Hussain, A. Al-Harrasi, G. Abba, N.U. Rheman, F. Mabood, I. Ahmed, M. Saleem, T. Van Ree, I.R. Green, S. Anwar, A. Badshah, A. Shah, I. Ali. The genus Pluchea: Phytochemistry, Traditional uses, and Biological activities. Chemistry & Biodiversity 10 (2011) 1944-1969. [3] Đoàn Thanh Tường, Phạm Hoàng Ngọc, Đỗ Đình Rãng. Nghiên cứu về một số cấu tử chính của tinh dầu Cúc tần. Thông báo khoa học Trường Đại học Sư phạm - Đại học Quốc gia Hà Nội 4 (199) (2015) 45-50. [4] Vũ Việt Nam, Trần Ngọc Ninh, Mc Leod J., Nguyễn Xuân Dũng, Kết quả nghiên cứu một số cây thuộc họ Cúc, Tạp chí Dược liệu 4 (2) (1999) 44-47. [5] Phan Minh Giang, Đỗ Thị Việt Hương, Nguyễn Ngọc Diệp, Nguyễn Mạnh Quyết, Một số hợp chất terpenoid và acid phenolic từ cây mẫn tưới, Tạp chí Dược liệu 23 (4) (2018) 195-199. [6] L.M. Khalilov, A.Z. Khalilova, A.E.R. Shakurova, I.F. Nuriev, A.S. Kachala, A.S. Shashkov, U.M. Dzhemilev. PMR and 13C NMR spectra of biologically active compunds. XII. Taraxasterol and its acetate from the aerial part of Onopordum acanthium. Chemistry of Natural Compounds 39 (3) (2003) 285-288. [7] L.J. Goad, T. Akihisha. Analysis of Sterols, Chapman & Hall, London, 1997. [8] Phan Minh Giang, Văn Thị Thanh Huyền, Đỗ Thị Việt Hương. Thành phần sterol, glycerol ester và thiophen trong cành cây cúc tần (Pluchea indica L.) của Việt Nam. Tạp chí Khoa học Đại học Quốc gia Hà Nội 34 (2) (2018) 78-82. https:// doi.org/10.25073/2588-1140/vnunst.4749. [9] B. Sing, S.N. Ram, V.B. Pandey, V.K. Joshi, S. S. Gambhir. Studies on antiinflammatory activity of taraxasterol acetate from Echinops echinatus in rats and mice, Phytotherapy Research 5 (3) (1991) 103-106. [10] Z. Krajcovicova, A. Vachálková, K. Horváthová. Taraxasterol and -sitosterol: New naturally compounds with chemoprotective/ chemopreventive effects, Neoplasma 51 (2004) 407-414. [11] J. Wang, M. Huang, J. Yang, X. Ma, S. Zheng, S. Deng, Y. Huang, X. Yang, P. Zhao. Anti-diabetic activity of stigmasterol from soybean oil by targeting the GLUT4 glucose transporter. Food & Nutrition Research 61 (1) (2017) 1364117.